Does schooling promote democracy? A meta-analysis. Issue 1 (2nd January 2023) - Ahmadov, Anar; Holstege, Floris
ABSTRACT: Worldwide democratic backsliding and surge of authoritarianism have revived interest in the potential of schooling to support democracy. Yet, while many intellectuals, donors, governments, and civil society organizations continue acting on this belief, the empirical literature they rely on is remarkably divided. We challenge this gridlock by offering a theoretical and methodological framework to account for conflicting findings and to facilitate resolving this debate. Our approach combines ideas on how different levels of schooling, ways of accounting for different contexts, and epistemic community influences can affect the relationship between education and political regime. To examine these ideas, we leverage statistical meta-analysis of synthesized empirical evidence base. Contrary to mainstream views, we find that, while the overall education-political regime relationship is positive, it is small and contingent. Pro-democratic effects of education come mostly from primary schooling and are uncertain beyond this level. Country-specific factors may explain part, though not all cross-national variation. Finally, we detect strong evidence of dissemination and publication biases that shape our knowledge on education-democracy linkage.